2016
DOI: 10.1039/c6gc00128a
|View full text |Cite
|
Sign up to set email alerts
|

Selective direct conversion of C5 and C6 sugars to high added-value chemicals by a bifunctional, single catalytic body

Abstract: The selective multi-step conversion of monosaccharides to anhydro-sugar alcohols was achieved in one-pot, one-stage by a bifunctional Ru catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 65 publications
3
43
0
2
Order By: Relevance
“…If these data confirmt hat the xylose conversion process is favored by hight emperatures, two justifications can be found for the observed selectivity trend. [139,140] Interception of the 2,5-anhydroxylose supports that, at least under our experimental conditions, the dehydration of xylose occurs through a" cyclic intermediates rearrangement" mechanism (Scheme 2), [141,142] which was suggestedt ob ee nergetically more favorable compared with a" dehydrationo fa cyclic intermediates" mechanism. On the other hand, it is known that xylose dehydration is faster than furfural loss reactions (e.g.,r esinification) at high temperatures, which is called "entropy effect".…”
Section: Chemical Compositionsupporting
confidence: 78%
See 1 more Smart Citation
“…If these data confirmt hat the xylose conversion process is favored by hight emperatures, two justifications can be found for the observed selectivity trend. [139,140] Interception of the 2,5-anhydroxylose supports that, at least under our experimental conditions, the dehydration of xylose occurs through a" cyclic intermediates rearrangement" mechanism (Scheme 2), [141,142] which was suggestedt ob ee nergetically more favorable compared with a" dehydrationo fa cyclic intermediates" mechanism. On the other hand, it is known that xylose dehydration is faster than furfural loss reactions (e.g.,r esinification) at high temperatures, which is called "entropy effect".…”
Section: Chemical Compositionsupporting
confidence: 78%
“…[138] Analogous findings have been reported for the two-fold dehydration reactionofs orbitol to isosorbide via 1,4-sorbitan. [139,140] Interception of the 2,5-anhydroxylose supports that, at least under our experimental conditions, the dehydration of xylose occurs through a" cyclic intermediates rearrangement" mechanism (Scheme 2), [141,142] which was suggestedt ob ee nergetically more favorable compared with a" dehydrationo fa cyclic intermediates" mechanism. [143,144] Nonetheless, we cannot rule out ac ontribution to the mechanism based on xylose-xylulose isomerization followed by dehydration,owing to the combined action of Lewis and Brønsted acid sites (Scheme 3).…”
Section: Chemical Compositionsupporting
confidence: 78%
“…[44] Am echanism similart ot hat described for the epimerization of xylitol to arabitol may be suggested by ad ehydrogenation-hydrogenation route. [48] It was proposed that the reaction starts with the reversible dehydrogenation of xylitol to xylose on the metal surface;t he isomerization of xylose to xylulose is catalyzedb yb ase [49] or Lewis acid sites [50] and then xylulose undergoes hydrogenation over the metal surface to arabitol. So, as the H 2 pressure increased, the dissolved H 2 concentration in the aqueous mediumw ill increaset or esult in more H 2 molecules that access the metal active site;t hus, the final hydrogenation step of unsaturated intermediates will be favored.T his behavior is also in accordance with results for the selectiveh ydrogenolysis of xylitolt oE Ga nd PG over Cu/SiO 2 at 200 8C, which showed that the selectivity to arabitol increaseda st he H 2 pressure increased.…”
Section: Screeningofrhc Atalysts For the Hydrogenolysis Of Ery At 200mentioning
confidence: 99%
“…[33][34][35] Moreover, Sor dehydration leads to the production of isosorbide, which can be used as a diol building block for a novel class of bio-polymers. [36][37][38] Industrially, Sor is synthesized from the hydrogenation of glucose, utilizing skeletal Ni catalysts. 33,39 Additionally, several noble metal-based catalytic systems have been reported for Glu hydrogenation in water, such as Ru (Ru/Al 2 O 3 , Ru/C, Ru/zeolite, and Ru/SiO 2 ) 35,[40][41][42][43][44][45] as well as Pt (Pt/Al 2 O 3 , Pt/SiO 2 , and Pt/C).…”
Section: Introductionmentioning
confidence: 99%